2006
DOI: 10.1002/cphc.200600310
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Sizing of a Sphere

Abstract: The size of a glass sphere positioned in the center of a microdisk electrode is determined by using a simple electrochemical procedure and is confirmed, additionally, by a microscopical measurement of the sphere at the time of the electrochemical measurement. The cyclic voltammetric response of the naked electrode and of the electrode with the sphere positioned in its center is recorded over a wide range of scan rates (0.002-1.5 V s(-1)). The size of the sphere is then determined by comparison of the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Voltammetric measurements could enable the size determination (see also Section 6.3.2.2.3) of single particles of known shape, such as a sphere on a microelectrode [57]. The respective microparticle is positioned centrally on a microelectrode, after which cyclic voltammetric measurements are recorded over a wider range of scan rates (e.g., from 2 mV s À1 to 1.5 V s À1 ).…”
Section: Voltammetric Sizing Of a Microparticle Spherementioning
confidence: 99%
“…Voltammetric measurements could enable the size determination (see also Section 6.3.2.2.3) of single particles of known shape, such as a sphere on a microelectrode [57]. The respective microparticle is positioned centrally on a microelectrode, after which cyclic voltammetric measurements are recorded over a wider range of scan rates (e.g., from 2 mV s À1 to 1.5 V s À1 ).…”
Section: Voltammetric Sizing Of a Microparticle Spherementioning
confidence: 99%
“…We recently have shown that cyclic voltammetric measurements as a function of voltage scan rate can provide a sensitive measurement of the radius of a sphere positioned in the center of a microelectrode [1]. We also reported the determination of the average size of inert particles at around the micron level by a simple procedure, in which they were deposited on a macroelectrode and cyclic voltammograms run on a redox couple present in solution as a function of voltage scan rate [2].…”
Section: Introductionmentioning
confidence: 98%
“…With a total mass of the particles and a value for their density, the accurate size was calculated [1]. We sized a spherical particle placed at the center of a microdisk electrode by comparing experimental voltammograms of a simple redox system at different scan rates with simulated voltammograms [5]. The same concept was extended to three dimensions by depositing a sphere adjacent to a microdisk electrode; chronoamperometric measurements of a simple redox system were compared with Lattice Boltzmann simulations to derive the radius of the sphere and its distance from the electrode.…”
Section: Introductionmentioning
confidence: 99%